Applications of Digital Signal Processing through Practical Approach - Radhakrishnan, Sudhakar (IntechOpen, 2015)
This book is recommended to readers who can ponder on the collection of chapters authored/co-authored by various researchers as well as to researchers around the world covering the field of digital signal processing. This book highlights current research in the digital signal processing area such as communication engineering, image processing and power conversion system. The entire work available in the book mainly focusses on researchers who can do quality research in the area of digital signal processing and related fields. Each chapter is an independent research, which will definitely motivate young researchers to further study the subject. These six chapters divided into three sections will be an eye-opener for all those engaged in systematic research in these fields.